TRANSFORMATION OF FIBROADENOMA TO PHYLLODES TUMOR AND THE USE OF ONCOPLASTIC TECHNIQUE FOR BREAST CONSERVATIVE TREATMENT - Prado, Julia Dias do; Vieira, Roberto José da Silva; Costa Neto, Waldyr Gomes da; Castro, Linda Lorena Gonzalez de; Flores, Bruno Bohrer; Velloso, Lea Pikelhaizen (Mastology, 2019)
Phyllodes tumors (PT) are rare neoplasms accounting for <1% of breast lesions. A transformation of a fibroadenoma (FA) to a PT is even more rare and unpredictable. Many challenges face PT management, since diagnostic through surgical treatment. We describe a case of a 63-year old woman with PT that was previously diagnosed as a FA who underwent an oncoplastic conservative surgery. A review of the literature on the diagnostic and surgical management of PT was performed. The diagnostic of PT can be hard mostly in needle biopsy, and the close follow up of negative lesions is recommended. Oncoplastic techniques might be an important tool on the conservative treatment of these patients.